Ungodly - Blake, Kendare (Blake, Kendare. Goddess war, 2015)
"For the Goddess of Wisdom, what Athena didn't know could fill a book. So the assault on Olympus left them beaten and scattered and possibly dead. So they have to fight the Fates themselves, who, it turns out, are the source of the gods' illness. And sure, Athena is stuck in the underworld, holding the body of the only hero she has ever loved. But Hermes is still topside, trying to power up Andie and Henry before he runs out of time and dies, or the Fates arrive to eat their faces"--